Relationship between Body Image and Body Dysmorphic Disorder in SPG Profession: Hubungan antara Citra Tubuh dan Gangguan Dismorfik Tubuh pada Profesi SPG - Sucianggala, Markus Alvin Suryanto; Wibowo, Doddy Hendro (Universitas Muhammadiyah Sidoarjo, 2021)
Physical changes that occur in adulthood, accept self-acceptance of the individual himself. This correlational study aims to see the relationship between body image and BDD tendencies in the sales promotion girl (SPG) profession. Participants selected using purposive sampling technique with participants as many as 134 participants. The measurement tool for body image research uses the Multi-dimensional Body Self Relation Questionnaire-Appearance Scales (MBSRQ-AS), while for BDD tendencies use a scale adapted from Africa which refers to aspects of Philips. Data is shared using google forms. The result was that there was a significant positive relationship between body image and BDD tendencies in the SPG profession. Impression value r = 0.721 with a significance of 0.000 (p <0.05). This means that the higher the body image that is owned, the higher the tendency of BDD to SPG. Highlights: Significant Correlation – A strong positive relationship (r = 0.721, p < 0.05) was found between body image and BDD tendencies in SPGs. Measurement Tools – Body image was assessed using MBSRQ-AS, while BDD tendencies were measured using a scale adapted from Africa based on Philips' aspects. Purposive Sampling – The study involved 134 SPGs selected through purposive sampling, with data collected via Google Forms. Keywords: Tendency of Body Dysmorphic Disorder (BDD), Body Image, Sales Promotion Girl (SPG)